SUBKLONING DAN ISOLASI GEN PENYANDI MIKRONEMA 3 (MIC-3) Toxoplasma gondii ISOLAT LOKAL - Diana Indrasanti; Aris Haryanto; Wayan T. Artama (Molekul, 2011)
Microneme protein (MIC) is one of proteins that belongs to excretory-secretory antigens (ESAs) of Toxoplasma gondii. Microneme 3 protein (MIC-3) is the protein that plays an important role in the invasion proccess during cell infection as a mediator attachment parasite to the host cell. The aim of this research is to clone mic3 (gene encoding for MIC-3) of T. gondii from local isolate using recombinant DNA technology by cloning mic3 in an expression vector. Deoxyribonucleic acid (DNA) from T. gondii tachyzoites was amplified by PuRe Taq RTG-PCR Beads using mic3 specific primers. Amplified DNA was double digested using EcoRV and HindIII restriction endonucleases and then purified using EZ-10 spin coloumn purification kit. The mic3 DNA was ligated into pET-32a(+) expression vector and transformated into Escherichia coli BL21. The results showed that recombinant mic3gene 4.2 kDa has been successfully performed by cloning gene encoding for MIC-3 protein of T. gondii local isolate into pET-32a(+) and transformed to E. coli BL21.